2019
DOI: 10.1213/ane.0000000000004534
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Double-Blinded Study of the Effect of Intravenous Ondansetron on the Effective Dose in 50% of Subjects of Prophylactic Phenylephrine Infusions for Preventing Spinal Anesthesia–Induced Hypotension During Cesarean Delivery

Abstract: BACKGROUND: Ondansetron has been shown to reduce the incidence of hypotension and vasopressor requirement during spinal anesthesia for obstetric and nonobstetric surgery. However, the magnitude of this effect has not been fully quantified. In this parallel-group, randomized, double-blinded study, we determined the effective dose in 50% of subjects (ED50) of a prophylactic phenylephrine infusion for preventing hypotension in patients who received a single dose of intravenous ondansetron 4 mg or sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…These findings may be attributable to the smaller dose of palonosetron used in their study which is having a sufficient effect on chemoreceptor trigger zone but being insufficient to affect the bupivacaine in the intervertebral space [19] . Effects similar to our study were concluded by Mowafi et al who studied the effects of IV granisetron on the sensory and motor blockade produced by intrathecal bupivacaine [20] and with Fassoulaki et al and Rashad MM et al who studied the effects of IV ondansetron on the spinal anesthesia [21,22] .…”
Section: Discussionsupporting
confidence: 91%
“…These findings may be attributable to the smaller dose of palonosetron used in their study which is having a sufficient effect on chemoreceptor trigger zone but being insufficient to affect the bupivacaine in the intervertebral space [19] . Effects similar to our study were concluded by Mowafi et al who studied the effects of IV granisetron on the sensory and motor blockade produced by intrathecal bupivacaine [20] and with Fassoulaki et al and Rashad MM et al who studied the effects of IV ondansetron on the spinal anesthesia [21,22] .…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that the ED50 for prophylactic phenylephrine in this study was nearly 0.1µg/kg/min higher than in our prior study, in which we found that the ED50s for prophylactic phenylephrine were 0.32 and 0.24 µg/kg/min for preventing spinal anesthesia-induced hypotension in the control group and experimental group, respectively. 19 The inconsistency of the ED50s between the two studies may be due to several protocol details, such as different intrathecal injection rates (10s vs over 15s) that subsequently resulted in different degrees of sympathetic blocks and a different incidence of hypotension and its severity. However, the significant differences between the experimental and control groups were similar in our two studies.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of ropivacaine for the following parturient was determined using the up-down allocation methodology. 10 , 11 Parturients were asked to report their pain on a standard VAS 30 min after administering the study solution. A VAS score ≤ 3 was defined as effective analgesia.…”
Section: Methodsmentioning
confidence: 99%
“…The EC50 of epidural ropivacaine was determined by calculating the mean values of the midpoints of pairs in parturients where an inadequate response was followed by an effective response (crossover), as previously described. 10 , 11 , 14 The Student’s t -test was used for comparing the EC50s. Overlapping CI methodology was used to test the differences in CIs for the EC50 values between the two groups.…”
Section: Methodsmentioning
confidence: 99%